The Influence of Entrepreneurial Passion on Entrepreneurial Behavior with the Mediation of Role Ambiguity among MSME Actors - Ezzani Maulaniya Ashohwa; R.Deni Muhammad Danial; Yanti Lestari Pujiastuti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
As MSMEs serve as an important contributor to Indonesia’s economic growth, understanding the psychological processes that connect entrepreneurial passion, role ambiguity, and entrepreneurial behavior is increasingly relevant. This study investigates the influence of entrepreneurial passion on entrepreneurial behavior by examining the mediating role of role ambiguity among MSMEs. The research aims to explore the relationships between entrepreneurial passion, role ambiguity, and entrepreneurial behavior within the context of local MSMEs. A quantitative associative research approach was applied using SEM-PLS analysis involving 100 respondents selected through a saturated sampling method. The results indicate that entrepreneurial passion has a positive and significant effect on role ambiguity, with a path coefficient of 0.837, a t-statistic value of 28.952, and a p-value of 0.000. Furthermore, role ambiguity positively and significantly influences entrepreneurial behavior, as shown by a coefficient of 0.423, a t-statistic of 6.489, and a p-value of 0.000. Entrepreneurial passion also has a direct positive effect on entrepreneurial behavior with a coefficient value of 0.570. At the same time, its influence is further strengthened through the mediating effect of role ambiguity, which produces an indirect effect of 0.354. These findings indicate that role ambiguity functions as a partial mediator in explaining how entrepreneurial passion contributes to entrepreneurial behavior.